A característica universal de Leibniz: contextos, trajetórias e implicações - Franzon, Carmen Rosane Pinto [UNESP] (2015)
During his life, Leibniz pursues the goal to create a universal language that perfectly communicates the thought and thus allows the knowledge of allthings. According to him, the viability to the construction of a universal language accrues from the fact that all the knowledge sustains itself on a finite number of basic concepts or simple ideas which can be identified and hierarchically structured. Inhis conceiving for the preparation of such language is necessary: defining the simple ideas; setting a proper system of signs -what he calls universal characteristic; and establishing the logical rules in order to compose complex ideas -or, as he's defined, rational grammar. We have defined the main goal of this paper as to present a survey on a universal language, in particular about theuniversal characteristicand to investigate the paths taken by Leibniz in this pursuit. From this purpose it courses the following secondary objectives: to verify how Leibniz develops his research in Binary Arithmetic, that consists on materialization of the universal characteristic; and briefly to present his rational grammar. To support our goal, we introduce some....